STILISTIKA DAN NILAI PENDIDIKAN KARAKTER NOVEL SEORANG LAKI-LAKI YANG KELUAR DARI RUMAH KARYA PUTHUT EA - Prarasto Miftahurrisqi; Suyitno Suyitno; Yant Mujiyanto (Universitas Sebelas Maret, 2018)
This research aims to describe the use of diction,the figure of speech, the use of image andcharacter education valuesin novel Seorang Laki-Laki Yang Keluar Dari Rumah by Puthut EA. This research employed descriptive qualitative approach with content analysis method. The data of research was contained in novel Seorang Laki-Laki Yang Keluar Dari Rumah and the result of interview with some informants. Technique of collecting data used was library and interview techniques. In this study, the author employed flow model of analysis.The results of research were as follows. Firstly, diction used in novel Seorang Laki-Laki Yang Keluar Dari Rumah consisted of six types. Secondly, there were four figure of speeches used in novel Seorang Laki-Laki Yang Keluar Dari Rumah. Ellipsis as the part of linking figure of speech is used most widely by author. Thirdly, the image used in novel Laki-Laki Yang Keluar Dari Rumah consisted of six types visual images were used most widely. Fourthly, there were ten character education values in novel Seorang Laki-Laki Yang Keluar Dari Rumah. Curiosity education character value was the one used most dominantly.